Correlation of some water quality parameters and Pb in sediment to gastropod diversity in Ambon Island Waters - Natan, Juliana; Hendrika, Nova; Limmon, Gino V; Rahman, Rahman (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
The coastal waters of Ambon Island have quite diverse ecosystems that allow for the presence of various organisms, one of which is gastropods. This study aims to analyze the correlation of some water parameters and Pb in sediment to the diversity of gastropods. The research method was carried out by observing the density, water quality parameters, and Pb metal in sediments. Water parameters were measured in situ and analyzed in the laboratory. The distribution of gastropods was analyzed through Principal Component Analysis (PCA). At the same time, the correlation analysis was carried out using the Pearson correlation approach using SPSS v.16. The results showed that the types of gastropods with the highest density in the waters of Ambon Island were Terebralia sulcata, Hebra corticata, and Nerita patula. While the species with the lowest density value were Nassarius olivaceus, Polinices didyma, Lunella cinerea, Conus eburneus, Cypraea isabella, Vexillum plicarium, and Columbella scripta. The Shannon-Wienner Diversity Index ranges from 1.253–2.622, and the diversity index ranges from 0.083-0.207. It was included in the low category caused by the disturbance of water pollution and Pb metal in sediments. Meanwhile, the dominance index ranged from 0.098 to 0.511 indicating species dominance at several observation stations. The waters' physical-chemical parameters strongly correlating with gastropod diversity are DO and Pb, with respective correlation values ​​of r = 0.656 and r = -0.785.